1996
DOI: 10.1007/bf02110652
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial inner membrane anion channel is inhibited by DIDS

Abstract: The mitochondrial inner membrane anion channel (IMAC) is a channel, identified by flux studies in intact mitochondria, which has a broad anion selectivity and is maintained closed or inactive by matrix Mg2+ and H+. We now present evidence that this channel, like many other chloride/anion channels, is reversibly blocked/inhibited by stilbene-2,2'-disulfonates. Inhibition of malonate transport approaches 100% with IC50 values of 26, 44, and 88 mu M for DIDS, H2-DIDS, and SITS respectively and Hill coefficients <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 33 publications
4
49
0
Order By: Relevance
“…Similarly, the agonist FGIN-1-27 (2-aryl-3-indoleacetamide) binds with high affinity to the mBzR but not to the central BzR (23). The mBzR inhibitors are known to block mitochondrial IMAC, as originally described in swelling assays of isolated mitochondria (24,25), and were later shown to block anion channels in single-channel patch clamp studies of isolated mitoplasts (26). We have also confirmed that 5-50 µM concentrations of PK11195 and 4′-Cl-DZP block mitochondrial inner membrane ion channels in cardiac mitoplasts (data not shown).…”
Section: Figuresupporting
confidence: 74%
“…Similarly, the agonist FGIN-1-27 (2-aryl-3-indoleacetamide) binds with high affinity to the mBzR but not to the central BzR (23). The mBzR inhibitors are known to block mitochondrial IMAC, as originally described in swelling assays of isolated mitochondria (24,25), and were later shown to block anion channels in single-channel patch clamp studies of isolated mitoplasts (26). We have also confirmed that 5-50 µM concentrations of PK11195 and 4′-Cl-DZP block mitochondrial inner membrane ion channels in cardiac mitoplasts (data not shown).…”
Section: Figuresupporting
confidence: 74%
“…The mitochondrial electron transport chain generates ROS, which are then transported into the cytoplasm through voltage-dependent anion channels. The mitochondrial anion channel inhibitor, DIDS, protects cells from oxidative injury by blocking the egress of mitochondrial ROS into the cytoplasm (30). We show that DIDS substantially decreases ROFA-AEC surfactant gelation, implicating mitochrondrial ROS in surfactant gelation.…”
Section: Discussionmentioning
confidence: 74%
“…We next characterized the contribution of mitochondrial-derived ROS to ROFA-AEC surfactant gelation by coincubating A549 cells with the mitochondrial anion channel inhibitor, 4,4Ј diisothiocyanatostilbene-2, 2Јdisulfonic acid (DIDS) (10 M) during ROFA exposure (30)(31)(32). A549 cells treated with DIDS alone showed no increase in surfactant gelation ( Figure 3B, filled squares).…”
Section: Mitochondrial-derived Ros Contribute To Rofa-aec Surfactant mentioning
confidence: 99%
“…Anion channels have been described in both the inner and outer mitochondrial membranes (Ballarin and Sorgato, 1996;Colombini et al, 1996). An inhibitor of these channels such as 4,4'-diisothiocyanato-stilbene-2,2'-disulfonate (DIDS) can suppress the egress of superoxide from the mitochondria (Beavis et al, 1996). Figure 1a shows that DIDS abolished the increase in DCF¯uorescence observed during hypoxia.…”
Section: Hypoxia Increases Mitochondrial Generation Of Reactive Oxygementioning
confidence: 98%